Volume 7: Polar and Arctic Sciences and Technology 2020
DOI: 10.1115/omae2020-18731
|View full text |Cite
|
Sign up to set email alerts
|

Peridynamic Analysis of Fragmentation of Ice Plate Under Explosive Loading With Thermal Effects

Abstract: Along with the development in arctic region, the icebreaking technologies are gradually becoming the focus. As one of the most powerful and effective way to breaking ice, especially in the ability to solve ice jams, the study of the behaviour of the sea and river ice under dynamic loads is an urgent subject of scientific research and it attracts extensive attention. In addition, the temperature change in the process of ice failure cannot be neglected since that temperature plays an important role in the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…because it has no restriction on the Poisson ratio, ensures stable computing, and is the most widely used of the three forms in engineering [15,[17][18][19][20][21].…”
Section: Fundamentals Of Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…because it has no restriction on the Poisson ratio, ensures stable computing, and is the most widely used of the three forms in engineering [15,[17][18][19][20][21].…”
Section: Fundamentals Of Pdmentioning
confidence: 99%
“…( 19); Relocated the particle according to Eq. (18). Yes P1←0 FIGURE 12 Flowchart of the contact detection algorithm presented in Figure 11 5.…”
Section: Yesmentioning
confidence: 99%
“…However, m is suggested to be 3 or 3.015 in most PD application literature (Madenci and Oterkus, 2014;Silling and Askari, 2005;Wang et al, 2020). Moreover, the PD application in ice simulation (Vazic et al, 2019;Wang et al, 2018a;Zhang et al, 2020) has also demonstrated that the 3.015 is the optimum value for m. Therefore,…”
Section: D Ice Sphere Impactmentioning
confidence: 99%